Microalgae and Biochar Agro-Fertilization of the Palestinian Rehan Barley Cultivar under Salinity Stress - Ashwaq A. Najjar; Arnd J. Kuhn; Sharaf M. Al-Tardeh; Christina M. Kuchendorf (Agronomy, 2021)
The efficient transfer of nutrients to plants in the form of biofertilizers on poor substrate was investigated. Biochar and dried algae biomass as well as mineral fertilizer were used to test the growth of the Palestinian ‘Rehan’ barley cultivar under salinity stress (4, 8, and 16 mS/cm EC). Rehan cultivar showed resilience to moderate levels of salinity and could still grow under high salinity stress (16 mS/cm EC). Rehan barley possessed better growth at early growth stage under the applied biofertilizers such as dried freshwater algal biomass (Chlorella vulgaris) and nutrient-laden biochar. It showed better growth than wheat (ssp. scirocco) under the same conditions. Its growth was highly improved by biochar treatment in low and moderate salinity conditions. Moreover, the combined effect between biochar and dried algae biomass could improve Rehan barley growth, but less than the effect of each biofertilizer separately. The biofertilizers affected most plant growth parameters under the salinity level of 4 and 8 mS/cm EC positively, while the growth declined again at 16 mS/cm EC. Overall, the biochar treatment showed the same effect as the mineral fertilizer on most of the parameters. The dried algae biomass and biochar also affected soil conditions. The highest soil water content (15.09%) was found in algae biomass treatments with 16 mS/cm EC. Biochar with 8 and 16 mS/cm EC had the highest pH value (8.63) near the rhizospheres. The nitrogen level was highest in the bottom soil sample (0.28 g N/kg soil) for biochar with 0 and 4 mS/cm EC. Meanwhile, the phosphate concentration was the highest (3.3 mg PO3−2/kg soil) in algae fertilizer treatments with 0 mS/cm EC in the bottom soil sample and lowest (4.14 mg PO3−2/kg soil) for the biochar with 8 mS/cm EC. The dried algae biomass and the biochar treatments can subsequently be viewed as conditioner substrates for improving the quality and fertility of the soil. Where possible, they should be considered as complement or replacement of mineral and manure fertilization to improve the impact on soil and environment.